Study of the parameters used in the encapsulation of commercial pectinase in calcium alginate and its effect on its catalytic activity - Flávio de Souza Neves CARDOSO (Food Science and Technology, 2019)
Abstract Despite the high catalytic properties of pectinases, the utilization of free enzymes always presents some hindrances such as low stability, a difficulty for product recovery and the impossibility of continuous use. Enzyme encapsulation is one of the methods used to overcome these limitations; however, some kind of effect is expected to occur on its catalytic activity. The objective of this work was to study the parameters involved in the process of encapsulation of a commercial pectinase product in calcium alginate and the effect of this encapsulation on its catalytic activity. The effect of the parameters of sodium alginate, calcium chloride, enzyme concentration and reaction time on enzymatic activity and encapsulation yield were also evaluated. The effect of pH and temperature on the activity of the free and encapsulated enzyme was studied. The highest yield of immobilization was obtained with a concentration of enzyme solution of 4%. Free and encapsulated enzymes showed similar behavior regarding the catalytic activity. The encapsulated enzyme had a narrower pH range (pH 4.0) than the free enzyme (pH 3.0 to 5.0). Besides, the encapsulated enzyme showed an increase in the stability in the pH range between 7 and 8 and above 10 to 12.